Pengaruh Stres Kerja Dan Beban Kerja Terhadap Kinerja Perawat Dengan Pemberian Kompensasi Sebagai Variabel Intervening Pada Rumah Sakit Umum Daerah Arosuka Kabupaten Solok - Nazwa Cyntia Utari; Desi Permata Sari; Silvia Sari (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine the effect of work stress and workload on nurse performance through compensation as an intervening variable at Arosuka Regional General Hospital, Solok Regency. The method used is quantitative. The study used primary data (questionnaires) from 89 nurse respondents at Arosuka Regional General Hospital, Solok Regency. The analysis method used is Structural Equation Modeling Analysis with Partial Least Square (PLS) 3.0. The results of this study indicate that, there is a significant influence of work stress on compensation, there is a significant influence of workload on compensation, there is a significant influence of work stress on nurse performance, there is a significant influence of workload on nurse performance, there is a significant influence of compensation on nurse performance, compensation is able to mediate the influence of work stress on nurse performance, compensation is able to mediate the influence of workload on nurse performance at Arosuka Regional General Hospital, Solok Regency.